Trends in Income Inequality, Pro-Poor Income Growth and Income Mobility - Stephen P. Jenkins; Philippe van Kerm (Institute for the Study of Labor (IZA), 2003)
We provide an analytical framework within which changes in income inequality over time are related to the pattern of income growth across the income range, and the reshuffling of individuals in the income pecking order. We use it to explain how it was possible both for ?the poor? to have fared badly relatively to ?the rich? in the USA during the 1980s (when income inequality grew substantially), and also for income growth to have been pro-poor. Income growth was also pro-poor in Western Germany, more so than in the USA, and inequality did not rise as much.
Keywords: I32; D31; 330; inequality; income growth; income mobility; pro-poor growth; reranking; Einkommensverteilung; Soziale Mobilität; Gini-Koeffizient; Schätzung; Deutschland; Vereinigte Staaten